The Impact of Regulation on the Availability and Profitability of Auto Insurance in Canada - Kelly, Mary; Kleffner, Anne; Li, Si (Assurances et gestion des risques / Insurance and Risk Management)

(untitled) (Faculté des sciences de l’administration, Université Laval, 2013)
This article investigates the impact of automobile insurance regulation on the size of the involuntary insurance market as well as the level and volatility of auto insurance loss ratios in Canada. We find that rate reduction orders, product reform and a pricing “Grid” that establishes maximum premiums increase the size of the involuntary market, while prior approval does not have any significant effect. In addition, unlike U.S. studies, we find that prior approval does not significantly impact loss ratio volatility. Our models also incorporate the impact of macroeconomic variables that proxy for the underwriting cycle and investment returns. The results suggest that the insurance underwriting cycle and stock market returns appears to be as important in determining insurers’ usage of the involuntary market as regulation. Taken together, our results suggests that regulatory interventions aimed at addressing affordability issues may have the unintended consequence of aggravating availability issues, and underlying market conditions may exacerbate this effect.